ANALISIS KINERJA KEUANGAN GUNA MEMPREDIKSI KEBANGKRUTAN PADA PERUSAHAAN PERTAMBANGAN JAKARTA ISLAMIC INDEX - Aris Sunandes (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2016)
Bankruptcy is a serious problem, there should be an early warning system that can detect potential bankruptcy earlier. The purpose of the research is using financial report to predict bankruptcy on mining companies listing in Jakarta Islamic Index. Altman model to assess the company's financial performance to predict the bankruptcy of a mining company accordance Jakarta Islamic Index. The results is companies with good category 13.33%, critical category 33.33% and 53.34% of potential bankruptcy. PT. Indo Tambangraya Tbk. good company in 2011-2012 and three years in critical condition. PT. Adaro Energy Tbk. in 2011 with critical condition and 2012-2015 in the potential bankruptcy category. PT. Vale Indonesia Tbk. in 2011 with critical condition and 2012-2015 in the potential bankruptcy category.